Processo formativo de professores: da experiência do clube de matemática a regência de classe - Hundertmarck, Jucilene (2017)
This master's dissertation research is part of the studies about teacher education and it was developed in the research line Formação, Saberes e Desenvolvimento Profissional, which is part of the Graduation Program of Education at Universidade Federal de Santa Maria. The main purpose is to investigate the teacher training in the Mathematics Club based on the perspective of Cultural Historical Theory. The Mathematics Club is a training space where some actions are studied, organized and developed collectively regarding the teaching of Mathematics in Early Childhood Education and in the Early Years of Elementary School. In order to achieve these purposes some research actions were stablished: to identify the main results pointed out by the studies that refer to the Mathematics Club based on the Historical-Cultural perspective, with emphasis on teacher training; to summarise the organization of the Mathematics Club at UFSM, through the reports from 2009 to 2016; to identify some moments of the training process considered meaningful by the teachers who have participated of the Mathematics Club and to verify how the Mathematics Club may contribute to the teacher training process. These actions were organized in two moments: first, the State of the Art about the researches conducted about the Mathematics Club in Brazil based on the perspective of Historical-Cultural Theory and the production of data with teachers who developed actions in the Mathematics Club in the Education Center at Universidade Federal de Santa Maria (UFSM) during their initial training. Therefore, it was made a mapping of the investigations carried out within the scope of the Mathematics Club of three institutions, as well as it was applied a questionnaire and a reflexive session with subjects who were participants of the Mathematics Club at UFSM. In conclusion, we have established some linkages between what these two moments point to. The results point to the building of a collective teaching identity, as well as the importance of a solid theoretical methodological proposal combined with the approach of the future teacher with situations close to the teaching practice.